Lipid Accumulation Product: a Simple and Accurate Index for Predicting Metabolic Syndrome in Patients with Adult Growth Hormone Deficiency - Chan, L.; Xue, H.; Xiaoya, Z.; Jiajia, X.; Wei, R.; Linman, L.; Qing, L.; Lan, L. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Purpose: It has been demonstrated that metabolic risk factors were increased in adult growth hormone deficiency (AGHD) patients. Lipid accumulation product (LAP) is a novel biomarker of central lipid accumulation related to risk of metabolic syndrome (MS), diabetes and cardiovascular disease. The aim of this study was to investigate the ability of LAP to identify MS in AGHD Patients.Materials and methods: In this cross-sectional study, 75 AGHD patients and 75 controls matched with age and gender were enrolled. The general anthropometries and blood biochemical indexes were measured. Body mass index(BMI), waist-hip ratio (WHR), LAP, HOMA-IR were calculated. Receiver operating characteristic (ROC) analysis was used to find out the cut-off points of LAP to predict MS.Results: Compared with control group, waist circumference (WC), WHR, Systolic blood pressure (SBP), Diastolic blood pressure (DBP), total cholesterol (TC), triglyceride (TG) and LAP were increased in AGHD group, while high density lipoprotein cholesterol (HDL-c) level was lower in AGHD group (P<0.05). The prevalence of MS was 41.3% in AGHD patients. AGHD patients with MS had significantly higher LAP levels compared to those without MS. LAP was highly correlated with components of MS. ROC analysis showed that LAP was a significant discriminator for MS in AGHD patients, and the optimal cutoff point of LAP to predict MS was 44.96 (96.8% sensitivity, 86.4% specificity).Conclusions: LAP was associated with MS and had a strong and reliable diagnostic accuracy for MS in AGHD patients.
Keywords: adult growth hormone deficiency (AGHD); lipid accumulation product (LAP); metabolic syndrome (MS)